Clinical and Bacteriological Profile of Neonatal Septicaemia at A Community Level Medical College Hospital (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Septicaemia is a significant cause of morbidity and mortality in neonates. Meningitis is a serious problem in newborns with high mortality and frequent neurological sequelae. In neonates, signs and symptoms of infections are often obscure and clinical examination cannot distinguish septicaemic babies with or without meningitis. Therefore, lumbar puncture is often not done in time and thus diagnosis of meningitis is missed. Our aim was to see the association of bacterial meningitis in neonatal septicaemia and their clinical and bacteriological profile. This study was performed at the neonatal ward of Kumudini Women’s Medical College Hospital from August 2007 to July 2009. All admitted newborns diagnosed as septicaemia clinically were enrolled prospectively. Detailed history was taken, thorough clinical examination performed, and blood culture, CSF study and other relevant investigations were done. Patients received standard medical care and followedup daily till discharge/death. Among 86 suspected cases, 30 (34.9%) had positive blood culture. Common clinical presentations of culture-positive cases were poor feeding (86.7%), lethargy (70%), respiratory distress (56.7%), fever (46.7%), jaundice (33.3%), seizure (26.7%) and cyanosis (20%). Male child outnumbered the baby girls (1.7:1). Other risk factors were maternal fever during delivery, prolonged rupture of membranes, birth asphyxia and poor socioeconomic status. Majority (63.3%) of the cultures isolated gram-negative bacilli, most commonly Klebsiella pneumonia (16.7%), Pseudomonas sp. (16.7%), and Acinetobacter (10%). Staphylococcus aureus (20%) was most common among gram-positive organisms, followed by Streptococcus pneumoniae (10%); no Group B streptococcus was isolated. Associated meningitis was present in two cases (6.7%) and nine out of 30 culturepositive cases (30%) died. This study confirms that neonatal septicaemia is a major problem in perinatology with high case fatality. As associated meningitis is difficult to distinguish clinically, CSF study needs to be included in septicaemia screening. An alarming finding of the study is that high proportion of the organisms are resistant to most of the commonly used antibiotics, again emphasize the importance of judicious antibiotic use. DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9435 JBCPS 2011; 29(3): 143-150